KONSEKUENSI INFORMASI ASIMETRIS DALAM PERKREDITAN DAN PENANGANANNYA PADA LEMBAGA PERBANKAN (Fokus Ekonomi, 2011)
creditor. As an agent needs to carry out the mandate the principal (lender) based on the creditcontract agreed between the creditor with the debtor. But when lenders face high informationasymmetry, then it can not design a fair credit contract. Consequently agency conflicts betweencreditors with the debtor could occur, the price of credit to be expensive, a high credit risk.Consequences needs to be managed for example through an effective monitoring system, loancovenance, tightening regulation of Legal Lending Limit, Credit Rationing, guarantees and creditinsurance and debt restructuring.Key word: asymmetric information, agency, covenance loan, credit rationing, debt restructuring.